Exploring Trypanosoma cruzi transmission dynamics in an acute Chagas disease outbreak using next-generation sequencing (2024)
Background: Chagas disease (CD), caused by Trypanosoma cruzi, poses a major global public health challenge. Although vector-borne transmission is the primary mode of infection, oral transmission is increasingly concerning. Methods: This study utilized long-amplicon-based sequencing (long-ABS), focusing on the 18S rRNA gene, to explore T. cruzi’s genetic diversity and transmission dynamics during an acute CD outbreak in Colombia, an area without domestic infestation. Results: Analyzing samples from five patients and five T. cruzi-positive marsupial samples, we identified coinfections between T. cruzi and Trypanosoma rangeli, mixed T. cruzi DTUs, suggesting possible links between human and marsupial T. cruzi infections. Coexistence of TcI, TcIV and T. rangeli suggests marsupial secretions as the possible source of T. cruzi transmission. Our investigation revealed diversity loss in DTUs TcIV and T. rangeli in humans after infection and in marsupial samples after culture. Conclusion: These findings provide significant insights into T. cruzi dynamics, crucial for implementing control and prevention strategies. Graphical abstract: (Figure presented.)